Analisis Pengalaman Wisatawan ( Studi Kasus di Obyek Wisata Tawangmangu ) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT: In order to develop a tourist object which include an ecotourism object, the tourist level factor should be considered, because it can be used to induce the market aspect, The research which takes place in Tawangmangu tourist resort results the following. (1) The Tawangmangu tourist resort is included in LaWid Mountain's ecosystem where Pinus merkusi dominates the vegetation structure and composition and where flora and fauna diversities are relatively not high.' (2) Parameters influencing the tourist experience level are lodscape, facilities, crown coverage, flora and fauna diversities and natural diffulfiesâ¢ (3) There are two tourist objects and attractions classifications in general